THE ROLE OF LANGUAGE IN THE CONSTRUCTION OF NATIONAL NARRATIVE - Qosimova Saida Umidjon qizi; Abduramanova Diana Valerivna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Language plays a fundamental role in the construction of national narratives, serving as a key instrument in shaping collective identity, historical memory, and cultural unity. Through literature, media, education, and political discourse, language helps to define the story a nation tells about itself, highlighting significant events, figures, and ideals that form the foundation of national consciousness. It is a medium for expressing shared values, promoting solidarity, and reinforcing a sense of belonging among citizens. Language also shapes the way history is remembered, allowing certain events to be emphasized or marginalized, influencing how the past is understood and reconciled.